Influence of supporting electrolyte on electrochemical formation of copper nanoparticles and their electrocatalytic properties - Zurita, Noelia (2022)
Comparative analysis of copper nanoparticles (CuNPs) obtained by electrodeposition on highly oriented pyrolytic graphite (HOPG) substrates from different supporting electrolytes containing sulphate anions, was performed. Voltammetric results indicated that Cu electrodeposition follows a diffusion-controlled nucleation and crystal growth model for three solutions studied (Na2SO4, H2SO4 and Na2SO4+H2SO4). Na2SO4 solution was most effective because the copper reduction occurs at the most positive potential value, reaching the highest current density. Analysis of potentiostatic current transients revealed that the process can be described predominantly by a model involving a 3D-progressive nucleation mechanism, which was corroborated by scanning electron microscopy (SEM) analysis. SEM images showed a high density of hemispherical shaped Cu particles of different sizes (mostly between 80-150 nm), randomly distributed on the HOPG surface for Na2SO4 electrolyte solution. In the presence of H2SO4, the size dispersion decreased, resulting in particles with greater diameters (up to 339 nm). The electrolyte solution with Na2SO4+H2SO4 revealed lower particle density with a considerable crystal size dispersion, where very small crystallites are prevailing. Cyclic voltammetry was used to evaluate qualitatively the catalytic activity of CuNPs deposited from three electrolyte solutions towards the nitrate reduction reaction. An enhanced catalytic effect was obtained when copper particles were prepared from either Na2SO4 or H2SO4 supporting electrolyte.